Can structured counselling and adherence tools improve adherence to immunosuppressive therapy in renal transplant patients? - angelene.vanderwesthuizen@up.ac.za (University of Pretoria, 2013)
Dissertation (MSc (Pharmacology))--University of Pretoria, 2009.